KAITAN SPIRITUAL INTELLIGENCE DENGAN PEMAKNAAN DAN PELAKSANAAN NILAI DI SEKOLAH - HANUM, FARIDA (FOUNDASIA, 2015)
Every subject matters contains the elements of value and meaning, and is very good to give them to the students. Through this knowledge, they have been invited from the beginning to develop their spiritual intelligence. In order to develop the spiritual intelligence, the process of education should make the students to he common to ask "why"; to try to find the relationship among the present things, to find the meaning behind and within something in order that they can feel some more things that they have studied to be useful and meaningful for their living, either at this moment or at the next moment.